Analisis Tingkat Kepuasan Pelanggan SPBU XYZ Gresik dengan Metode Service Quality (Servqual ) dan Importance Performance Analysis (IPA) - Adymas Trenaldy Pramu Bintoro; Elly Ismiyah; Moh. Jufriyanto (Universitas Islam Raden Rahmat, Malang, 2024)
This research was conducted at XYZ gas station with the aim of 1). Knowing the value of customer satisfaction and GAP that occurs in each service attribute, 2). Mapping service attributes on a Cartesian diagram based on satisfaction and expectation values, 3). Provide improvement proposals for service attributes that have the highest GAP. Based on the results of the study, it can be obtained that the average satisfaction level of 5 servqual dimensions is 3.42 and the average expectation level of 5 servqual dimensions is 3.38 so that a positive GAP value of 0.04 is obtained. The highest dimensional GAP was identified in the reliability dimension (reability) which has a value of -0.20. Based on the IPA results of 19 indicators, there are 6 indicators that should be the main priority of the gas station because they are in quadrant I, which shows that the indicators in the quadrant are considered important by customers but the performance of the XYZ gas station is actually low and not appropriate.